Pembentukan Kreativitas Siswa melalui Metode Project Based Learning di SMP Regina Pacis Surakarta - Bagus Susetyo; Antonius Edi Nugroho (Program Studi Pendidikan Musik FBS UNP, 2023)
Purpose: The process of doing this project is expected to shape student creativity through problem-solving skills with project-based learning methods. The objectives of this study include: 1) analyzing the application of project-based learning methods at Regina Pacis Surakarta Middle School; 2) examining the results of student creativity in learning Music Arts using project-based learning methods at Regina Pacis Middle School Surakarta. The research method used is qualitative with descriptive exposure. The procedures carried out in this study include 1) selecting themes, topics and cases by looking for phenomena based on previous research, theory or observations, 2) determining the theoretical basis and reviewing the literature, 3) formulating research focus and problems, 4) data collection, carried out using observation, interviews and documentation, 5) data analysis, 6) data validity in the form of data triangulation, 7) conclude. Method: This study compared information provided by the media with interviews and direct observation at Regina Pacis Surakarta Middle School at different times. Method triangulation was carried out by comparing information or data obtained through interviews and observations of informants. Result and Discussion: Researchers conclude from the results of interviews and observations. Then the formulation results are matched with previous research, books and other journal articles. The results of the evaluation carried out by the teacher showed that students exceeded the passing mark, and the success of teaching and learning activities using project-based learning methods at SMP Regina Pacis Surakarta had a percentage of 85% - 90%. This percentage is also the result of this study.